Concise synthesis of heliolactone, a non-canonical strigolactone isolated from sunflower. Issue 6 (2nd June 2020) - Yamamoto, Shunya; Atarashi, Taiki; Kuse, Masaki; Sugimoto, Yukihiro; Takikawa, Hirosato
ABSTRACT: Heliolactone is one of the earliest identified non-canonical strigolactones. Its concise synthesis was achieved by employing Knoevenagel-type condensation and semi-reduction of a malonate intermediate as the key steps. This synthesis was performed in a non-stereoselective manner, and thus a racemic and diastereomeric mixture of heliolactone was obtained. The developed synthetic route is fairly concise and straightforward. Abstract: : Graphical abstract A racemic and diastereomeric mixture of heliolactone was synthesized.